Nanocrystalline germanium nip solar cells with spectral sensitivities extending into 1450 nm. (4th January 2017) - Li, Chang; Ni, Jian; Sun, Xiaoxiang; Wang, Xinyu; Li, Zhenglong; Cai, Hongkun; Li, Juan; Zhang, Jianjun
Abstract: To absorb the infrared part of the solar spectrum more efficiently, narrow bandgap hydrogenated nanocrystalline germanium (nc-Ge:H) thin films were fabricated by radio frequency plasma enhanced chemical vapor deposition at a low temperature of 180 °C. While the incubation layer of the nc-Ge:H was reduced to less than 5 nm by using the ultra-high hydrogen dilution, the negative photoconductivity behavior was still observed as the thickness of nc-Ge:H up to 30 nm. Therefore, as the best candidate for solar cells application, the nc-Ge:H (20 nm)/nc-Si:H (10 nm) periodic multilayer structure was prepared and used as the absorption layer of nc-Ge:H nip solar cells. More importantly, the spectral sensitivities extending into the wavelength of 1450 nm were achieved in the nc-Ge:H nip solar cells. In addition, the annealing for the nc-Ge:H nip solar cells was carried out. While the overall short circuit current density of the device is improved after 500 °C annealing, the spectral sensitivities in the infrared region is decreased due to the the coalescence of Ge crystallites.